Effects of Sub-Lethal High Pressure Homogenization Treatment on the Adhesion Mechanisms and Stress Response Genes in Lactobacillus acidophilus 08 - Braschi, Giacomo; D’Alessandro, Margherita; Gottardi, Davide; Siroli, Lorenzo; Patrignani, Francesca; Lanciotti, Rosalba (Frontiers in Microbiology, 2021)
Cell surface hydrophobicity and adhesion are very important phenotypical traits for probiotics that confer them a competitive advantage for the resilience in the human gastrointestinal tract. This study was aimed to understand the effects over time of a 50 MPa hyperbaric treatment on surface properties of Lactobacillus acidophilus 08 including cell surface hydrophobicity, autoaggregation, in vitro adhesion (mucin layer and Caco-2 cells). Moreover, a link between the hurdle applied and the expression of genes involved in general stress response (groEL, clpP) and adhesion processes (efTu, slpA) was evaluated. High pressure homogenization (HPH) at 50 MPa significantly increased the cell surface hydrophobicity percentage (H %), autoaggregation and in vitro adhesion on mucin of L. acidophilus 08 cells compared with untreated samples. Moreover, the hyperbaric hurdle induced an up regulation of the stress response genes groEL and ef-TU together with a down regulation of clpP and S-layer slpA genes. Looking at the protein profile, HPH-treatment showed an increase in the number or intensity of protein bands at high and low molecular weights